Prevalencia de Leishmaniásis cutánea en la Parroquia Progreso del cantón Pasaje, provincia de El Oro en el segundo semestre del 2003 - Veintimilla Cabanilla, Betty M. (2007)
It is a zoonosis caused by protozoa of the leishmania gender and it is considered by the O. M. S. like one of the six more important tropical illnesses. According to MarinKelle (1980) he/she is considered that it exists 12’000.000 in the Old and New world, with approximately 400.000 new cases registered per year.